PENGARUH PERSONAL SELLING DAN DISTRIBUSI TERHADAP KUANTITAS PENJUALAN PADA PT. KARYA JAYA SUKSES PRIMA - Yuslinda Nasution (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2017)
PT. Bekasi Jaya Sukses Karya Prima is an authorized distributor from XL that covers East Bekasi and surrounding area. Based on the results of the research, the researcher suggests some problems in the implementation of its business activitiesthat is, not the achievement of sales targets and the decrease in sales volume.The purpose of this research to determine the implementation of personal selling, and distribution in order to determine how much influence on the quantity of sales. To achieve these objectives, the authors conducted research at PT. Karya Prima Jaya Sukses Bekasi from November 2014.Data were collected through questionnaires to 30 respondents employee which are taken randomly and simple. As for analyzing the data, the authors use the method of multiple regression analysis, analysis of multiple correlation coefficient, determination coefficient analysis, test T and Test F. The results were obtained regression equation y = 68,0723 + 0,005841583 x1 + 0,013714475 x2 .shows that personal selling and distribution give a low positive effect on the quantity of sales.Based on t test and f test concluded that each variable does not significantly affect the quantity of sales, and based on the results of calculations using the formula coefficient of determination, it can be seen that the contribution of personal selling and distribution of the sales volume was 4.26% and the remaining 95.74% influenced by other factors.